Ecology and restoration potential of Ruppia maritima in a managed mosquito impoundment of the Indian River Lagoon, Florida, USA - Deanna F. Webber; Richard E. Mulroy; Patrick H. Monaghan; David C. Heuberger; M. Dennis Hanisak; Rachel A. Brewton (Regional Studies in Marine Science, 2026)

Assessment of a Baited Remote Underwater Video Method to Evaluate American Lobster ( Homarus americanus ) Response to Baits in Nature - L. Grace Walls; Rachel Webber; Laura Brady; Michelle Hodgson; Iain J. McGaw; Russell C. Wyeth (Fisheries Management and Ecology, 2026)
The American Lobster ( Homarus americanus ) is the target of an extensive fishery in the Northwest Atlantic, yet there is no systematic method for evaluating relative performance of baits for the fishery. We used Baited Remote Underwater Video (BRUV) to assess lobster attraction to commercial baits versus natural prey. Significantly higher counts of lobsters in BRUV with commercial baits (herring, mackerel, and rock crab) matched expectations from catches in the fishery. Although location, substrate type, month, and year of deployment also affected lobster counts, the effect of bait type did not depend on any of these potentially confounding factors. Thus, we infer that BRUV can be used to compare lobster responses to different bait types regardless of when or where deployed, providing a useful tool for future initial testing of alternative baits before validation in the fishery.

Beyond Climate Change: The Role of Integrated Soil Fertility Management for Sustaining Future Maize Yield in Sub‐Saharan Africa - Antoine Couëdel; Gatien N. Falconnier; Myriam Adam; Rémi Cardinael; Johan Six; Moritz Laub; Alex C. Ruane; Kenneth Boote; Eric Justes; Ward N. Smith; Anthony M. Whitbread; François Affholder; et al. (Global Change Biology, 2026)
Climate change is projected to exacerbate food insecurity in sub‐Saharan Africa (SSA) by reducing crop yields and soil fertility. Many climate change impact studies in SSA have overlooked long‐term effects of soil fertility on crop yield. We evaluated maize yields under different scenarios of soil fertility (using soil organic carbon as a proxy) and climate change (considering changes in temperature, rainfall, and CO 2 ) at four sites in SSA. Using an ensemble of 15 calibrated soil‐crop models, we found a strong consensus that, without fertilization, soil fertility declines over time, impacting maize yields more strongly than changes in temperature, rainfall, or CO 2 . The model ensemble indicated that when accounting for soil fertility changes, the yield benefits of combined application of organic and mineral inputs increase over time, even under climate change. These findings highlight the importance of considering long‐term change in soil fertility when assessing impacts of climate change and integrated nutrient management on crop production in SSA.

It's not all about PFAS: Metal(loid)s are associated with physiological and metabolic changes in a native frog from conservation wetlands - Damian C. Lettoof; Rui Wang; Brad Clarke; Nicola Gray; Samuele Sala; Nick Bourne; William R. Richmond; Helen E. Nice; Peter Novak; Brenton von Takach; Bruce L. Webber; Anna H. Kaksonen; et al. (Environmental Pollution, 2025)

Cold lenses in the Amundsen Sea: impacts of sea ice formation on subsurface pH and carbon - Daisy D. Pickup; Dorothee C. E. Bakker; Karen J. Heywood; Francis Glassup; Emily M. Hammermeister; Sharon E. Stammerjohn; Gareth A. Lee; Socratis Loucaides; Bastien Y. Queste; Benjamin G. M. Webber; Patricia L. Yager (Ocean Science, 2025)
The Amundsen Sea polynya hosts intense sea ice formation, but, due to the presence of relatively warm and salty modified Circumpolar Deep Water, the cold, brine-enriched water is not typically dense enough to sink to the deep ocean. A hydrographic survey of the Dotson Ice Shelf region in the Amundsen Sea using two ocean gliders identified and characterised subsurface lenses containing water with temperatures less than −1.70 °C. These lenses, located at depths between 240 to 500 m, were colder, saltier and denser than the overlying Winter Water (WW) layer. The pH of the lenses was 7.99, lower than WW by 0.02 and the dissolved inorganic carbon concentration was higher in the lenses than WW by approximately 10 µmol kg−1. The lenses were associated with a dissolved oxygen concentration greater than surrounding water at the same depth and density due to the cold temperatures increasing O2 solubility. We hypothesise that these lenses are a product of wintertime surface cooling and brine rejection in areas with intense sea ice formation. They may form in shallow regions, potentially around the Martin Peninsula and Bear Island, where intense upper ocean heat loss occurs, and then spill off into the deeper Dotson-Getz Trough to reach their neutrally-buoyant depth. This is supported by wintertime temperature and salinity observations. This study highlights the importance of shallow parts of shelf seas for generating cold dense water masses in the warm sector of Antarctica. These lenses are widespread in the region of the Dotson-Getz Trough and have the potential to sequester carbon deeper than typical in the region, alongside cooling the water impinging on the Dotson ice shelf base.

Wheat crop models underestimate drought stress in semi-arid and Mediterranean environments - H. Webber; D. Cooke; C. Wang; S. Asseng; P. Martre; F. Ewert; B. Kimball; G. Hoogenboom; S. Evett; A. Chanzy; S. Garrigues; A. Olioso; et al. (Field Crops Research, 2025)

Ecosurveillance reveals subtle metabolic effects on the non-native cane toad (Rhinella marina) from low levels of accumulated environmental per- and polyfluoroalkyl substances - Damian C. Lettoof; Marina Suzuki; Sandra Nilsson; Thao V. Nguyen; Nicholas Bourne; Cassandra L. Pegg; Sally Stockwell; Utpal Bose; Jacob Devine; Tyler Contor; Bruce L. Webber; Anna H. Kaksonen; et al. (Environmental Pollution, 2025)

Fine-scale mapping of ocean user groups to support species and habitat spatial management - Owen M. Exeter; Julian Branscombe; Annette C. Broderick; Tom Hooper; Jan Maclennan; Trudy Russell; Kate Sugar; Alice Trevail; Julie Webber; Kristian Metcalfe (Marine Policy, 2025)

Past and future wheat yield losses in France’s breadbasket - Rogério de S. Nóia-Júnior; Pierre Martre; Jean-Charles Deswarte; Jean-Pierre Cohan; Marijn Van der Velde; Heidi Webber; Frank Ewert; Alex C. Ruane; Tamara Ben-Ari; Senthold Asseng (Field Crops Research, 2025)

Consistent Individual Differences and Plasticity in Migration Behaviour of Three North American Ungulates - Michel P. Laforge; Eric Vander Wal; Quinn M. R. Webber; Chris Geremia; Matthew J. Kauffman; Douglas E. McWhirter; Arthur Middleton; Tony W. Mong; Kevin L. Monteith; Anna C. Ortega; Hall Sawyer; Jerod A. Merkle (Ecology Letters, 2025)
Migratory herbivores often time spring migration to coincide with the green‐up of plants. When the timing of green‐up changes across years, herbivores can respond directly and be plastic to changing conditions or populations may adapt via inherent differences among individuals that may allow for an evolutionary response. We quantified plasticity and individual variation in the timing of spring migration and selection for high‐quality forage as a function of the timing of spring green‐up using behavioural reaction norms for three North American ungulate species. The timing of arrival to summer range (but not departure from winter range) was plastic to the timing of green‐up, and both arrival and departure timing were repeatable. Our results suggest that herbivores synchronise migration with the timing of green‐up by adjusting the pace of migration and may be buffered against change via individual differences. Quantifying plasticity and differences in responses represents a crucial step to elucidating the fate of species in a changing world.

Utilisation of macroalgal habitats by juvenile rabbitfishes on an inshore reef - Cecilia C. Martin; Eva C. McClure; Kelsey Webber; Martina Burgo; Andrew S. Hoey (Coral Reefs, 2024)
Macroalgal beds are increasingly recognised as nursery habitats for coral reef fish; however, the extent to which they are used as a source of food and/or a refuge from predation remains largely unexplored. Here, we investigate the distribution, feeding behaviour, diet, and predation risk for juvenile rabbitfish in macroalgal habitats on Orpheus Island, Great Barrier Reef. Visual surveys revealed that juvenile and adult Siganus doliatus had different among-habitat distributions with juveniles being largely restricted to the reef flat and positively associated with macroalgal cover, while adults were abundant on the reef crest. Focal feeding observations show that within macroalgal habitats, juvenile S. doliatus targeted epiphytes on Sargassum (80% of bites), with relatively few bites taken on turfs or the Sargassum itself (27% and 8%, respectively). These observations were supported by stomach content analyses with filamentous algae being the dominant item in the stomach content of both small (< 4 cm total length, TL; 58%) and large juvenile S. doliatus (> 4 cm TL; 47%). The stomach content of juvenile S. doliatus, S. canaliculatus, and S. spinus collected from macroalgal habitats was similar, consisting primarily of filamentous algae and detritus. We found no relationship between the abundance of potential predators and juvenile rabbitfishes across the study sites. Collectively, our results suggest that juvenile rabbitfishes are using macroalgal habitats on this, and potentially other, inshore reefs as a food source and add to a growing body of literature highlighting the importance of these habitats for the early life stages of reef fish.

Environmental DNA methods for biosecurity and invasion biology in terrestrial ecosystems: Progress, pitfalls, and prospects - Karen L. Bell; Mariana Campos; Benjamin D. Hoffmann; Francisco Encinas-Viso; Gavin C. Hunter; Bruce L. Webber (Science of The Total Environment, 2024)

Long-term soil organic carbon and crop yield feedbacks differ between 16 soil-crop models in sub-Saharan Africa - Antoine Couëdel; Gatien N. Falconnier; Myriam Adam; Rémi Cardinael; Kenneth Boote; Eric Justes; Ward N. Smith; Anthony M. Whitbread; François Affholder; Juraj Balkovic; Bruno Basso; Arti Bhatia; et al. (European Journal of Agronomy, 2024)

The extreme 2016 wheat yield failure in France - Rogério de S. Nóia Júnior; Jean‐Charles Deswarte; Jean‐Pierre Cohan; Pierre Martre; Marijn van der Velde; Remi Lecerf; Heidi Webber; Frank Ewert; Alex C. Ruane; Gustavo A. Slafer; Senthold Asseng (Global Change Biology, 2023)
France suffered, in 2016, the most extreme wheat yield decline in recent history, with some districts losing 55% yield. To attribute causes, we combined the largest coherent detailed wheat field experimental dataset with statistical and crop model techniques, climate information, and yield physiology. The 2016 yield was composed of up to 40% fewer grains that were up to 30% lighter than expected across eight research stations in France. The flowering stage was affected by prolonged cloud cover and heavy rainfall when 31% of the loss in grain yield was incurred from reduced solar radiation and 19% from floret damage. Grain filling was also affected as 26% of grain yield loss was caused by soil anoxia, 11% by fungal foliar diseases, and 10% by ear blight. Compounding climate effects caused the extreme yield decline. The likelihood of these compound factors recurring under future climate change is estimated to change with a higher frequency of extremely low wheat yields.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Delta-9-tetrahydrocannabinol reduces willingness to exert effort in women - Margaret C. Wardle; Elisa Pabon; Heather E. Webber; Harriet de Wit (Psychopharmacology, 2022)

Progress in understanding of Indian Ocean circulation, variability, air–sea exchange, and impacts on biogeochemistry - Helen E. Phillips; Amit Tandon; Ryo Furue; Raleigh Hood; Caroline C. Ummenhofer; Jessica A. Benthuysen; Viviane Menezes; Shijian Hu; Ben Webber; Alejandra Sanchez-Franks; Deepak Cherian; Emily Shroyer; et al. (Ocean Science, 2021)
Over the past decade, our understanding of the Indian Ocean has advanced through concerted efforts toward measuring the ocean circulation and air–sea exchanges, detecting changes in water masses, and linking physical processes to ecologically important variables. New circulation pathways and mechanisms have been discovered that control atmospheric and oceanic mean state and variability. This review brings together new understanding of the ocean–atmosphere system in the Indian Ocean since the last comprehensive review, describing the Indian Ocean circulation patterns, air–sea interactions, and climate variability. Coordinated international focus on the Indian Ocean has motivated the application of new technologies to deliver higher-resolution observations and models of Indian Ocean processes. As a result we are discovering the importance of small-scale processes in setting the large-scale gradients and circulation, interactions between physical and biogeochemical processes, interactions between boundary currents and the interior, and interactions between the surface and the deep ocean. A newly discovered regional climate mode in the southeast Indian Ocean, the Ningaloo Niño, has instigated more regional air–sea coupling and marine heatwave research in the global oceans. In the last decade, we have seen rapid warming of the Indian Ocean overlaid with extremes in the form of marine heatwaves. These events have motivated studies that have delivered new insight into the variability in ocean heat content and exchanges in the Indian Ocean and have highlighted the critical role of the Indian Ocean as a clearing house for anthropogenic heat. This synthesis paper reviews the advances in these areas in the last decade.

Acute drug effects differentially predict desire to take dextroamphetamine again for work and recreation - Jennifer K. Hoots; Heather E. Webber; Cecilia Nunez; Jessica A. Cooper; Paula Lopez-Gamundi; Victoria M. Lawlor; Scott D. Lane; Michael T. Treadway; Margaret C. Wardle (Psychopharmacology, 2021)

Occurrence of environmental contaminants (pesticides, herbicides, PAHs) in Australian/Queensland Apis mellifera honey - Natasha L. Hungerford; Mary T. Fletcher; Heng Hang Tsai; Darina Hnatko; Lorinda J. Swann; Cassandra L. Kelly; Shalona R. Anuj; Ujang Tinggi; Dennis C. Webber; Stephen T. Were; Benjamin L. L. Tan (Food Additives & Contaminants Part B-Surveillance, 2021)

Delineating the organization of projection neuron subsets in primary visual cortex with multiple fluorescent rabies virus tracing - Liang Li; Yajie Tang; Leqiang Sun; Jinsong Yu; Siheng Zhang; Hui Gong; Hannah C. Webber; Xiaoyu Zhang; Zhe Hu; Xiangning Li; Khaista Rahman; Xiangwei Shi; et al. (Brain Structure and Function, 2021)

Modelling climate change impacts on maize yields under low nitrogen input conditions in sub‐Saharan Africa - Gatien N. Falconnier; Marc Corbeels; Kenneth J. Boote; François Affholder; Myriam Adam; Dilys S. MacCarthy; Alex C. Ruane; Claas Nendel; Anthony M. Whitbread; Éric Justes; Lajpat R. Ahuja; Folorunso M. Akinseye; et al. (Global Change Biology, 2020)
Smallholder farmers in sub‐Saharan Africa (SSA) currently grow rainfed maize with limited inputs including fertilizer. Climate change may exacerbate current production constraints. Crop models can help quantify the potential impact of climate change on maize yields, but a comprehensive multimodel assessment of simulation accuracy and uncertainty in these low‐input systems is currently lacking. We evaluated the impact of varying [CO 2 ], temperature and rainfall conditions on maize yield, for different nitrogen (N) inputs (0, 80, 160 kg N/ha) for five environments in SSA, including cool subhumid Ethiopia, cool semi‐arid Rwanda, hot subhumid Ghana and hot semi‐arid Mali and Benin using an ensemble of 25 maize models. Models were calibrated with measured grain yield, plant biomass, plant N, leaf area index, harvest index and in‐season soil water content from 2‐year experiments in each country to assess their ability to simulate observed yield. Simulated responses to climate change factors were explored and compared between models. Calibrated models reproduced measured grain yield variations well with average relative root mean square error of 26%, although uncertainty in model prediction was substantial (CV = 28%). Model ensembles gave greater accuracy than any model taken at random. Nitrogen fertilization controlled the response to variations in [CO 2 ], temperature and rainfall. Without N fertilizer input, maize (a) benefited less from an increase in atmospheric [CO 2 ]; (b) was less affected by higher temperature or decreasing rainfall; and (c) was more affected by increased rainfall because N leaching was more critical. The model intercomparison revealed that simulation of daily soil N supply and N leaching plays a crucial role in simulating climate change impacts for low‐input systems. Climate change and N input interactions have strong implications for the design of robust adaptation approaches across SSA, because the impact of climate change in low input systems will be modified if farmers intensify maize production with balanced nutrient management.

Selective Sensory Axon Reinnervation and TRPV1 Activation - T. Poitras; A. Chandrasekhar; L. McCoy; P. Komirishetty; A. Areti; C. A. Webber; Douglas W. Zochodne (Molecular Neurobiology, 2019)

Global wheat production with 1.5 and 2.0°C above pre‐industrial warming - Bing Liu; Pierre Martre; Frank Ewert; John R. Porter; Andy J. Challinor; Christoph Müller; Alex C. Ruane; Katharina Waha; Peter J. Thorburn; Pramod K. Aggarwal; Mukhtar Ahmed; Juraj Balkovič; et al. (Global Change Biology, 2019)
Efforts to limit global warming to below 2°C in relation to the pre‐industrial level are under way, in accordance with the 2015 Paris Agreement. However, most impact research on agriculture to date has focused on impacts of warming >2°C on mean crop yields, and many previous studies did not focus sufficiently on extreme events and yield interannual variability. Here, with the latest climate scenarios from the Half a degree Additional warming, Prognosis and Projected Impacts (HAPPI) project, we evaluated the impacts of the 2015 Paris Agreement range of global warming (1.5 and 2.0°C warming above the pre‐industrial period) on global wheat production and local yield variability. A multi‐crop and multi‐climate model ensemble over a global network of sites developed by the Agricultural Model Intercomparison and Improvement Project (AgMIP) for Wheat was used to represent major rainfed and irrigated wheat cropping systems. Results show that projected global wheat production will change by −2.3% to 7.0% under the 1.5°C scenario and −2.4% to 10.5% under the 2.0°C scenario, compared to a baseline of 1980–2010, when considering changes in local temperature, rainfall, and global atmospheric CO 2 concentration, but no changes in management or wheat cultivars. The projected impact on wheat production varies spatially; a larger increase is projected for temperate high rainfall regions than for moderate hot low rainfall and irrigated regions. Grain yields in warmer regions are more likely to be reduced than in cooler regions. Despite mostly positive impacts on global average grain yields, the frequency of extremely low yields (bottom 5 percentile of baseline distribution) and yield inter‐annual variability will increase under both warming scenarios for some of the hot growing locations, including locations from the second largest global wheat producer—India, which supplies more than 14% of global wheat. The projected global impact of warming

Primary care providers’ lived experiences of genetics in practice - Brittany Harding; Colleen Webber; Lucia Ruhland; Nancy Dalgarno; Christine M. Armour; Richard Birtwhistle; Glenn Brown; June C. Carroll; Michael Flavin; Susan Phillips; Jennifer J. MacKenzie (Journal of Community Genetics, 2019)

Climate change impact and adaptation for wheat protein - Senthold Asseng; Pierre Martre; Andrea Maiorano; Reimund P. Rötter; Garry J. O’Leary; Glenn J. Fitzgerald; Christine Girousse; Rosella Motzo; Francesco Giunta; M. Ali Babar; Matthew P. Reynolds; Ahmed M. S. Kheir; et al. (Global Change Biology, 2019)
Wheat grain protein concentration is an important determinant of wheat quality for human nutrition that is often overlooked in efforts to improve crop production. We tested and applied a 32‐multi‐model ensemble to simulate global wheat yield and quality in a changing climate. Potential benefits of elevated atmospheric CO 2 concentration by 2050 on global wheat grain and protein yield are likely to be negated by impacts from rising temperature and changes in rainfall, but with considerable disparities between regions. Grain and protein yields are expected to be lower and more variable in most low‐rainfall regions, with nitrogen availability limiting growth stimulus from elevated CO 2 . Introducing genotypes adapted to warmer temperatures (and also considering changes in CO 2 and rainfall) could boost global wheat yield by 7% and protein yield by 2%, but grain protein concentration would be reduced by −1.1 percentage points, representing a relative change of −8.6%. Climate change adaptations that benefit grain yield are not always positive for grain quality, putting additional pressure on global wheat production.

Color patterns in white‐beaked dolphins ( Lagenorhynchus albirostris ) from Iceland - Chiara G. Bertulli; Anders Galatius; Carl C. Kinze; Marianne H. Rasmussen; William Keener; Marc A. Webber (Marine Mammal Science, 2016)
Few studies have examined the natural complex pigmentation patterns of white‐beaked dolphins. From 2002 to 2014, whale‐watching trips in Iceland provided a platform of opportunity to collect a large body of photographs of free‐ranging individuals from a single area of distribution for this species. Based on 823 images, 571 individuals showing one or more color components were identified, and assigned to the following four age classes: adults ( n = 437), juveniles ( n = 109), calves ( n = 14), and neonates ( n = 11). A total of 26 color components were observed and described: seven terms previously applied to white‐beaked dolphins, 12 previously applied to other dolphin species, and seven newly defined terms. Results showed that each age class could be positively identified by differences in specific color components, some of which were exclusive. Therefore, color patterns may prove useful in estimating maturity in free‐ranging white‐beaked dolphins. This tool could be further refined through assessment of a wide sample of freshly stranded specimens of known sex and age, which could reveal new age class‐specific components, as well as sexually dimorphic characteristics not seen here. Geographic variation should be investigated by comparing image data sets and stranded animals from different parts of the North Atlantic.

The reproductive advantages of a long life: longevity and senescence in wild female African elephants - Phyllis C. Lee; Victoria Fishlock; C. Elizabeth Webber; Cynthia J. Moss (Behavioral Ecology and Sociobiology, 2016)

A Perspective on the Clinical Translation of Scaffolds for Tissue Engineering - Matthew J. Webber; Omar F. Khan; Stefanie A. Sydlik; Benjamin C. Tang; Robert Langer (Annals of Biomedical Engineering, 2015)

Cardiovascular responses in older adults with total knee arthroplasty at rest and with exercise on a positive pressure treadmill - Sandra C. Webber; Karla J. Horvey; Madison T. Yurach Pikaluk; Scott J. Butcher (European Journal of Applied Physiology, 2014)

Essential elements of discourse for advancing the modelling of species' current and potential distributions - Darren J. Kriticos; David C. Le Maitre; Bruce L. Webber (Journal of Biogeography, 2013)
A recent review by Dormann et al . (2012, Journal of Biogeography , 39 , 2119–2131) has proposed that methods for the modelling of species distributions be considered as a continuum. We disagree with this thesis, and contend that attempting to present the diverse range of methods as a continuum is unhelpful and ultimately not convincing. It adds to the confusion about the strengths and weaknesses of the diversity of available modelling methods, what exactly it is that they model, and the most appropriate applications. We highlight variation within and between modelling methods that is obscured by the continuum framework and propose that context of application and clarity of method are critical elements for future discourse on the topic.

Latitudinal variation in blue tit and great tit nest characteristics indicates environmental adjustment - Mark C. Mainwaring; Ian R. Hartley; Stuart Bearhop; Kaat Brulez; Christopher R. du Feu; Gerald Murphy; Kate E. Plummer; Simone L. Webber; S. James Reynolds; D. Charles Deeming (Journal of Biogeography, 2012)
Aim The laying of eggs and the building of a nest structure to accommodate them are two of the defining characteristics of members of the class Aves. Nest structures vary considerably across avian taxa and for many species the structure of the completed nest can have important consequences both for parents and their offspring. While nest characteristics are expected to vary adaptively in response to environmental conditions, large‐scale spatial variation in nest characteristics has been largely overlooked. Here, we examine the effects of latitudinal variation in spring temperatures on nest characteristics, including insulatory properties, and reproductive success of blue tits, Cyanistes caeruleus , and great tits, Parus major . Location Great Britain. Methods Nests and reproductive data were collected from seven study sites, spread over 5° of latitude. The nest insulatory properties were then determined before the nests were separated into nest base material and cup lining material. Results As spring temperatures increased with decreasing latitude, the mass of the nest base material did not vary in either species, while the mass of the cup lining material and nest insulatory properties decreased in both species. This suggests that in response to increasing temperatures the breeding female reduces the mass of the cup lining material, thereby maintaining an appropriate microclimate for incubating and brooding. The mean first egg date of both species advanced with decreasing latitude and increasing spring temperatures, although clutch size and brood size at hatching and fledging did not vary. Main conclusions This is the first study to demonstrate that the nest‐construction behaviour of birds varies in response to large‐scale spatial variation in ambient temperatures. Therefore, nest composition reliably indicates environmental conditions and we suggest that studies of nest structure may be sentinels for the early signs of rapid climate change.

Neural field model of binocular rivalry waves - Paul C. Bressloff; Matthew A. Webber (Journal of Computational Neuroscience, 2012)

Global assessment of experimental climate warming on tundra vegetation: heterogeneity over space and time - Sarah C. Elmendorf; Gregory H. R. Henry; Robert D. Hollister; Robert G. Björk; Anne D. Bjorkman; Terry V. Callaghan; Laura Siegwart Collier; Elisabeth J. Cooper; Johannes H. C. Cornelissen; Thomas A. Day; Anna Maria Fosaa; William A. Gould; et al. (Ecology Letters, 2012)
Ecology Letters (2011) Abstract Understanding the sensitivity of tundra vegetation to climate warming is critical to forecasting future biodiversity and vegetation feedbacks to climate. In situ warming experiments accelerate climate change on a small scale to forecast responses of local plant communities. Limitations of this approach include the apparent site‐specificity of results and uncertainty about the power of short‐term studies to anticipate longer term change. We address these issues with a synthesis of 61 experimental warming studies, of up to 20 years duration, in tundra sites worldwide. The response of plant groups to warming often differed with ambient summer temperature, soil moisture and experimental duration. Shrubs increased with warming only where ambient temperature was high, whereas graminoids increased primarily in the coldest study sites. Linear increases in effect size over time were frequently observed. There was little indication of saturating or accelerating effects, as would be predicted if negative or positive vegetation feedbacks were common. These results indicate that tundra vegetation exhibits strong regional variation in response to warming, and that in vulnerable regions, cumulative effects of long‐term warming on tundra vegetation – and associated ecosystem consequences – have the potential to be much greater than we have observed to date.

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

Recombinant TCR Ligand Reverses Clinical Signs and CNS Damage of EAE Induced by Recombinant Human MOG - Sushmita Sinha; Sandhya Subramanian; Ashley Emerson-Webber; Maren Lindner; Gregory G. Burrows; Marjorie Grafe; Christopher Linington; Arthur A. Vandenbark; Claude C. A. Bernard; Halina Offner (Journal of Neuroimmune Pharmacology, 2010)

Adapting the CROPGRO model for saline soils: the case for a common bean crop - H. A. Webber; C. A. Madramootoo; M. Bourgault; M. G. Horst; G. Stulina; D. L. Smith (Irrigation Science, 2010)

Generation of large droplet aerosols within microbiological containment using a novel flow-focussing technique - Richard J. Thomas; Daniel Webber; William Sellors; Aaron Collinge; Andrew Frost; Anthony J. Stagg; Stephen C. Bailey; Pramukh N. Jayasekera; Rosa R. Taylor; Steve Eley; Richard W. Titball (Aerobiologia, 2009)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

Monitoring of Particle Mass and Number in Urban Air - N Pomeroy; D Webber; C Murphy (Environmental Monitoring and Assessment, 2000)

A whole-genome radiation hybrid panel and framework map of the rat genome - Linda C. McCarthy; Marie-Therese Bihoreau; Susanna L. Kiguwa; Julie Browne; Takeshi K. Watanabe; Haretsugu Hishigaki; Atsushi Tsuji; Susanne Kiel; Caleb Webber; Maria E. Davis; Catherine Knights; Angela Smith; et al. (Mammalian Genome, 2000)

Seed cone production enhanced by injecting 38-year-old Larix occidentalis Nutt. with GA4/7 - Raymond C. Shearer; Michael U. Stoehr; Joe E. Webber; Stephen D. Ross (New Forests, 1999)

Zooplankton growth rates: the influence of size and resources in tropical marine copepodites - R. R. Hopcroft; J. C. Roff; M. K. Webber; J. D. S. Witt (Marine Biology, 1998)

HTLV-I antibody studies in villagers in East Sepik Province, Papua New Guinea - R. C. Sanders; A. Levin; G. Anian; I. Webber; H. Lee; P. Swanson; A. Diwan; R. Desowitz; W. A. Blattner; M. P. Alpers (Archives of Virology, 1990)

DDT contamination of benthic macroinvertebrates and sediments from tributaries of Wheeler Reservoir, Alabama - E. Cliff Webber; D. R. Bayne; W. C. Seesock (Archives of Environmental Contamination and Toxicology, 1989)